ADOLESCENCE: REASONS TO INDUCE ABORTION (Fiep Bulletin - online, 2014)
Sex education at school points to the importance of the teacher's role in the prevention of arising problems from the exercise of sexuality in adolescence. The magnitude of the problems from pregnancy and abortion on these ages justifies the current study that has as its objective to identify the reasons that cause adolescent students to have an abortion. The aforementioned study, which used the analysis theory of thematic content for categories of the answers, showed as the main reasons for abortion the fear of their parents, the unwanted pregnancy, and the rejection of their partner. Data which corroborates the literature studied about this subject as well as the family's role and the importance of dialogue and sex education at school.
Keywords: adolescents; abortion; sex education